Effect Concentrations of Polyethylene Glycol in Stability Structure of Blending Polymer Cholesteryl acrylate-ITO - Afrizal Afrizal; Arif Rahman; Iwan Sugiharto; Muhammad Ismail (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Polymer ChoAcry/ITO was added glycol is one of the material polymer liquid crystal modifications. In general polymer liquid crystal cholesteryl acrylate was made for many application usage in optoelectronics materials. This research want to study effect Polyethylene Glycol (PEG) in polymer choAcry/ITO for stability structure of blending choAcry/ITO. PEG 0.006 was added to mixed cholesteryl acrylate with ITO. Polymerizations that doing using UV curing photopolymerizations. Characterizations group functions using Fourier Transformed Infra Red (FTIR) and Nuclear Magnetic Resonance (NMR). Effect concentrations of PEG in PolyChoAcry-ITO shown from FTIR spectrum, shown not different. Peak in spectrum showed are C=C and C-H aliphatic, C=C aromatic, C-O ester, and para-benzene. Based on data FTIR that PE-b-PEG not change structures. Therefore, diffractogram of XRD, showed added ITO and PEG can be affect phisycal and chemistry properties of polymer cholestryl acrylate. This data showed PEG changed structures of polymer. Polyethilene glycol spreading into polymer cholesteryl acrylate. In the literatures told that PEG can be conjunctionc between that monomer or polymer cholesteryl acrylate-ITO.